Marxism and the making of china a doctrinal History - Gregor, A. James; SpringerLink (Online service) (New York : Palgrave Macmillan US : Imprint: Palgrave Macmillan, 2014)
An assessment of the influence of the Marxism of Karl Marx and Friedrich Engels on revolutionary developments in China. The work covers the period from the first appearance of the Chinese Communist Party under Mao Zedong until its full transformation by Deng Xiaoping - into a nationalist, developmental, single-party, developmental dictatorship.
Keywords: Political science; Asia -- History; Political theory; World politics; Asia -- Politics and government; International relations; Political philosophy; Political Science and International Relations; Asian Politics; Political History; Asian History; Political Theory; Political Philosophy; International Relations